The Influence Of Inflation And Exchange Rates On The Balance Of Trade In Member Countries Of The Organization Of Islamic Cooperation (OKI) (Case Study: Indonesia, Brunei Darussalam And Saudi Arabia) - Widya Ayu Harahap; Imsar Imsar; Nur Ahmadi Bi Rahmani (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study aims to determine how much influence inflation and exchange rates have on the trade balance in 3 OIC member countries namely Indonesia, Brunei Darussalam, and Saudi Arabia Starting from 2012-2021. This research uses a quantitative approach with panel data types, The analysis tool used is Eviews 10 with the Vector Error Correction Model (VECM) method. Based on the results of this study shows that inflation and exchange rates have a significant effect on the trade balance in the 3 OIC member countries for the short term and also the long term. The variable which more dominantly affects the trade balance both in the short and long term is inflation. Where a low inflation rate will not have a significant effect on the trade balance so a low increase in inflation will still increase the balance sheet trade in 3 OIC member countries. The inflation rate can also cause a country not to be able to compete in world trade so exports decline and certainly affect the surplus trade balance in 3 OIC member countries.